Analysis of the bond-slip performance of steel bars and steel fiber recycled concrete based on the constitutive relationship model - Xia Zhengbing; Duan Xiaofang (Fracture and Structural Integrity)
In order to promote the application of steel fiber recycled concrete in road and bridge construction, 25 groups of steel fiber recycled concrete with different mix proportions were designed, taking the replacement rate of recycled aggregates and the volume fraction of steel fibers as experimental parameters, and 77 steel bars and steel fiber recycled concrete bonded specimens were made and pasted with strain gauges for the pull-out test. The research results showed that the greater the replacement rate of recycled aggregates was, the lower the bond strength between steel bars and steel fiber recycled concrete was; in the range of 0~1.2%, the higher the mixing amount of steel fibers was, the greater the bond strength of the specimen was; in the range of 0~1.6%, the higher the mixing amount of steel fibers was, the greater the slip value of the specimen under the peak load was; the addition of steel fibers improved the failure behavior of the recycled concrete pull-out specimens; the test specimens mainly had pull-out failure when the mixing amount of steel fibers was 1.2% and 1.6%. Finally, this study modified the bond-slip constitutive relationship model of steel and steel fiber recycled concrete, analyzed the influence of the replacement rate of recycled aggregates and the mix proportion of steel fibers on its bonding performance, and compared the results with the test results. The results demonstrate that the test curve is in good agreement with the fitted curve, which can provide theoretical support for engineering applications.